Association of Acute Kidney Injury with the Risk of Dementia: A Meta-Analysis - Hussain, Salman; Singh, Ambrish; Antony, Benny; Claure-Del Granado, Rolando; Klugarová, Jitka; Líčeník, Radim; Klugar, Miloslav (Journal of clinical medicine, 2021)
Acute kidney injury (AKI) is associated with several adverse outcomes, including new or progressive chronic kidney disease, end-stage kidney disease, and mortality. Epidemiological studies have reported an association between AKI and dementia as a long-term adverse outcome. This meta-analysis was aimed to understand the association between AKI and dementia risk. A literature search was performed in MEDLINE and Embase databases, from inception to July 2021, to identify epidemiological studies reporting the association between AKI and dementia risk. Title and abstract followed by the full-text of retrieved articles were screened, data were extracted, and quality was assessed, using the Newcastle-Ottawa scale by two investigators independently. The primary outcome was to compute the pooled risk of dementia in AKI patients. Subgroup analysis was also performed based on age and co-morbidities. Certainty of evidence was assessed using the GRADE approach. Statistical analysis was performed using Review Manager 5.4 software. Four studies (cohort (n = 3) and case-control (n = 1)) with a total of 429,211 patients, of which 211,749 had AKI, were identified. The mean age of the patients and the follow-up period were 64.15 ± 16.09 years and 8.9 years, respectively. Included studies were of moderate to high quality. The pooled estimate revealed a significantly higher risk of dementia in AKI patients with an overall relative risk/risk ratio (RR) of 1.92 (95% CI: 1.52-2.43), p ≤ 0.00001. Dementia risk increases by 10% with one year increase in age with an RR of 1.10 (95% CI: 1.09-1.11), p < 0.00001. Subgroup analysis based on stroke as a co-morbid condition also revealed significantly higher dementia risk in AKI patients (RR 2.30 (95% CI: 1.62-3.28), p = 0.009). All-cause mortality risk was also significantly higher in AKI patients with dementia with a pooled RR of 2.11 (95% CI: 1.20-3.70), p = 0.009. The strength of the evidence was of very low certainty as per the GRADE assessment. Patients with AKI have a higher risk of dementia. Further large epidemiological studies are needed to confirm the mechanistic association.
Keywords: meta-analysis; dialysis; acute kidney injury; dementia; epidemiology; systematic review